'I would love to blast some pow music and just dance': First Nations students' experiences of physical activity on a university campus. Issue 2 (14th March 2016) - Ferguson, Leah; Philipenko, Nadia
Abstract: Although physical activity is valued in Aboriginal communities, an in depth understanding of the physical activity experiences among urban Aboriginal people in Canada is absent from the literature. The primary purpose of this study was to explore First Nations students' physical activity experiences on a university campus. A secondary purpose was to identify ways to create and promote positive physical activity experiences for First Nations university students. Five First Nations students (ages = 18–28 years) engaged in a talking circle and one-on-one interviews. Three main themes emerged from the students' narratives: (1) we are similar but unique, (2) a longing for tradition, and (3) extending a personal connection with physical activity. The participants' stories included challenges with physical activity on campus, some of which were unique to the First Nations student experience (e.g. lack of traditional activities) and grew increasingly complex as their narratives unfolded (e.g. experiencing racism). The participants shared strategies they use to deal with challenges related to physical activity, including self-talk, incorporating significant others, and attempting to integrate traditional beliefs and practices. Changes made at the institutional-level were also considered as ways to manage personally difficult physical activity experiences. Further research and collaborative approaches are needed to: (1) develop university initiatives that generate more physical activity options as well as enhance the quality of physical activity for Aboriginal students, and (2) explore culturally-relevant resources that might be useful for Aboriginal students dealing with difficult physical activity experiences.